Management of Dyslipidemia - Aronow, Wilbert S. (IntechOpen, 2021)
Dyslipidemia is a major risk factor for cardiovascular events, cardiovascular mortality, and all-cause mortality. The earlier in life dyslipidemia is treated, the better the prognosis. The current book is an excellent one on dyslipidemia written by experts on this topic. This book includes 12 chapters including 5 on lipids, 4 on hypercholesterolemia in children, and 3 on the treatment of dyslipidemia. This book should be read by all health care professionals taking care of patients, including pediatricians since atherosclerotic cardiovascular disease begins in childhood.